2016
DOI: 10.2337/dc15-2331
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Variability in Glycemic Control Is Associated With White Matter Hyperintensities in APOE4 Genotype Carriers With Type 2 Diabetes

Abstract: OBJECTIVEWe assessed whether the apolipoprotein ε4 (APOE4) genotype affects the relationship of variability in long-term glycemic control (measured by HbA1c SD of multiple measurements) with white matter hyperintensities (WMHs) in elderly patients with type 2 diabetes (T2D).RESEARCH DESIGN AND METHODSWMH volume was generated from structural T1 and fluid-attenuated inversion recovery MRI in each subject. The analysis included 124 subjects; 27 (21.8%) had one or more APOE4 alleles.RESULTSHbA1c variability was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Finally, the number of study participants was relatively small. However, our sample size was largely comparable to that of a previous study that found that patients with AD-related pathological changes are susceptible to glucose changes associated with the progression of WMH ( Livny et al, 2016 ). Additional longitudinal studies with a large sample size may provide further evidence to confirm our findings.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Finally, the number of study participants was relatively small. However, our sample size was largely comparable to that of a previous study that found that patients with AD-related pathological changes are susceptible to glucose changes associated with the progression of WMH ( Livny et al, 2016 ). Additional longitudinal studies with a large sample size may provide further evidence to confirm our findings.…”
Section: Discussionmentioning
confidence: 61%
“…The pathogenesis of WMH is most likely driven by ischemia resulting from hypertensive small vessel disease, but amyloid angiopathy may also be another underlying cause of extensive WMH ( Tomimoto, 2015 ). More recently, carriage of the apolipoprotein E4 genotype was reported to affect the relationship between glucose alterations and WMH ( Livny et al, 2016 ; Cox et al, 2017 ). Thus, patients with AD have a variety of pathologies, including small vessel disease, and may be more susceptible to the effects of glucose exacerbation on WMH progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results were essentially unaffected by the inclusion of white matter hyperintensities (partial correlation for interaction on total frontal lobe r = −0.16; p = 0.03, and on superior frontal gyrus r = −0.16; p = 0.02). Similarly, additional secondary analyses added a cardiovascular risk composite to the primary model, which was the first principal component of a factor analysis consisting of systolic and diastolic blood pressure, LDL and HDL, cholesterol, and creatinine (26); or levels of inflammatory markers (CRP and Il-6). Results were mildly attenuated, and remained significant for the interaction of Hp genotype and depressive symptoms on total frontal lobe volume and superior frontal gyrus and trend level for the interaction on white matter hyperintensities volume (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Given that the fluctuation of the blood glucose levels seems to lead to the aggravation of various diseases, such as atherosclerosis and dementia, especially in elderly subjects (12, 19), we hypothesized that the fluctuation of the blood glucose levels was more closely associated with the remnant β-cell function in elderly subjects (≥65 years old) and examined this point in the present study. However, contrary to our expectations, no marked difference was noted in the results between relatively young subjects and elderly subjects.…”
Section: Discussionmentioning
confidence: 99%